|
|
Deriving sin(x),
cos(x),
sec^2(x),
-csc(x)cot(x),
sec(x)tan(x),
-csc^2(x)
: Desde las derivadas
Dando:
sin(x) = cos(x),
cos(x) = -sin(x),
tan(x) = sec^2(x),
csc(x)
= -csc(x)cot(x),
sec(x) = sec(x)tan(x),
cot(x)
= -csc^2(x).
Use el teorema fundamental de cálculo:
cos(x) =
sin(x), cos(x)
dx = sin(x) + c
-sin(x) =
cos(x), sin(x)
dx = -cos(x) + c
sec^2(x) =
tan(x), sec^2(x)
dx = tan(x) + c
-csc(x)cot(x) =
csc(x), csc(x)cot(x)
dx = -csc(x) + c
sec(x)tan(x) =
sec(x), sec(x)tan(x)
dx = sec(x) + c
-csc^2(x) =
cot(x), csc^2(x)
dx = -cot(x) + c
|
|
|